TIPOLOGI ÃLÃ AL-BÃB: ANALISIS SEMANTIK AYAT-AYAT ALQURAN DAN IMPLEMENTASINYA DALAM PENDIDIKAN ISLAM - Asmawi, Muhammad Nur (Hunafa: Jurnal Studia Islamika, 2008)
This paper deals with the concept of Ã»lÃ» al-bÃ¢b in the Qurâan. While studying the concept, thematic approach (tafsÃ®r maudÃ»âÃ®) and semantical analysis will be employed. The steps include collecting sixteen Quranic verses related to Ã»lÃ» al-bÃ¢b, classifying them according to typologies, and analyzing them. With these steps, a whole framework of this concept will be revealed, as well as the constructs of the term Ã»lÃ» al-bÃ¢b. Based on the grammatical analysis, the meaning of Ã»lÃ» al-bÃ¢b is constructed according to its position as munÃ¢da, fÃ¢âil, sifah and khabr. Based on this analysis, Ã»lÃ» al-bÃ¢b covers such meanings as al-rÃ¢sikhÃ»n fÄ« al-âlm, qawm yatafakkarÃ»n, ahl al-dhikr and ashÃ¢b al-âuqÃ»l. These meanings show educational activities which include principles and purposes, that is, to create knowledgeable-pious human beings, who are useful for humanity.Kata Kunci:Â Â  tipologi Ã»lÃ» al-bÃ¢b, al-dhikr, ayat Alquran, analisis semantik, pendidikan Islam